Democratizing Money ? debating legitimacy in monetary reform proposals - Weber, Beat. (Cambridge, 2018)
The Constitution of India embodies a moment of profound transformation one in which the subjects of an alien, colonial regime became the free citizens of a republic. Yet, this is the story of constitutions the world over. The Indian Constitution was, however, transformative in a second sense as well: it sought a thorough reconstruction of State and society itself. It recognized that, unlike in the West, the State had never been the only power centre in India. Deeply pervasive hierarchies were maintained by structures that took various forms caste, for instance and the State had limited authority to interfere. The Constitution, then, was intended to transform not just the political status of Indians from subjects to citizens, but also the social relationships on which legal and political edifices rested. This is reflected in its provision of fundamental rights enforceable against groups, communities and private parties a rarity in constitutions elsewhere even today, let alone in 1950. And it is such forms of transformative constitutionalism that have been at the heart of recent judgements, such as the decriminalization of same-sex relations and the striking down of colonial-era beggary laws. The Transformative Constitution is an attempt to understand and to give primacy to this original transformative vision of the Constitution. Gautam Bhatia interprets India s founding document in a way which is faithful to its text, structure, and history, and above all to its overarching commitment to political and social transformation. He picks out nine cases and analyses their judgements in painstaking detail in the context of seven decades worth of Indian jurisprudence to show how they advance the core principles of equality, fraternity, and liberty enshrined in it. This is a treatise that presents a new way of reading the Constitution as India approaches the seventieth anniversary of its adoption.
Keywords: Monetary Policy